TIPOLOGI KODIFIKASI KITAB HADIS AL-MAâA - Kudhori, Muhammad (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
The method which is used by theologian in hadi> th codification has a trend that changes from time to time. After third century of hijriyah, some theologians arrange hadi>thâs book using the method that has already taught to them before, but others have a different method. One of the methods which is dissimilar from others is hadi>th codification method or it is called Muâjam. Muâjam is a hadi> th codification typology that is based on the friend of the Prophetâs Musnad or the writerâs teacher that is arranged based on the alphabet. In some sample, it has seemed that Muâjamâs book also shows some friends of the Prophetâs biography before showing the history of them. Muâjamâs book is classified into two groups. They are Muâjam al-Shuyu>kh (based on teacherâs names) and Muâjam al-Saha>bah (based on friends of the Prophetâs names). Commonly, there is some quality of hadi>th s in Muâjamâs books. There are s}ah}i>h}, h}asan, d}aâi>f even mawd}u>â (false). One of the benefits in Maâajimâs book is as the main reference of Prophetâs Musnad hadi>th. It means continued until the Prophet himself and containing lots of hadi>th that is not found in al-Kutu>b al-Sittah. Moreover, Muâjamâs book is one of the main references to know the biography of Sahabat (friendâs Prophet), nasab (offspring), and their virtue.